Exploring Policies & Practices for The Private Sector to Advance Women’s Economic Empowerment and Prevent Gender Based Violence in Post-Conflict Countries - Helal, Amina (AUC Knowledge Fountain, 2023)
This study aims to investigate the role of the private sector in advancing women’s economic empowerment and gender-based violence prevention with a focus on post-conflict countries. It explores challenges facing them, and opportunities to be seized by governments and other stakeholders in this regard. The study also sheds light on the gap in the private sector’s awareness and commitment to achieve the UN Sustainable Development Goals (SDGs) and to implement the UN Women, Peace and Security (WPS) agenda in post-conflict countries. It explores the different possible engagements of the private sector in response to the research question. The thesis also sees the stakeholder theory as a relevant framework, particularly to analyze the private sector’s engagement with NGOs. It adopts a qualitative approach incorporating in-depth semi-structured online interviews with various participants from managers in private sector companies in post-conflict countries like South Sudan, Liberia and Somalia, to leadership of NGOs active in women’s economic empowerment and gender-based violence (GBV) prevention in Cambodia, Liberia, and the Horn of Africa region. In addition, interviews were conducted with Women, Peace and Security experts with extensive experience in analyzing governments’ priorities in this topic to explore the possible interventions from the private sector to be better engaged in the implementation of the agenda. The analysis shows that in post-conflict countries, NGOs that execute programs to support women’s economic empowerment and prevent GBV are overdependent on donor countries and international organizations to finance and sustain the implementation of their projects. They are therefore highly affected by the global change in funding priorities and feel the significant need of cooperating with private sector companies in this regard. The analysis also exposed that neither the private sector companies nor the post-conflict situations are homogeneous. The frequency of engagement to advance women’s empowerment differs greatly depending on the type of company, the incentives and the engagement modalities. Similarly, in countries in their early post-conflict phase, stakeholders’ priorities and challenges vary. Within the same vein, due to the high prevalence of GBV in these contexts, awareness campaigns are the most used type of strategies adopted by multinational private companies through their corporate social responsibility (CSR) programs. The study sheds light on the different roles played by the private sector, and reveals a myriad of challenges and opportunities to advance and facilitate it. The lack of accessibility to women because of the poor infrastructure, insecurity, the rural divide, as well as the lack of coordination and communication between NGOs and private companies remain key noted challenges that hinder the effective engagement of the private sector in these contexts. Furthermore, the findings showed that several existing CSR initiatives, and community development projects targeting women’s economic empowerment lack depth, and are not designed to accommodate women’s needs in post-conflict reconstruction situations. Thus, the thesis stresses the gap between the possible supply of support from the private sector and the existing demand either from the actors involved in advancing women’s issues (such as UN agencies, the NGOs, or the women beneficiaries directly). At the normative level, the involvement of the private sector in the implementation of the WPS agenda has also been found underleveraged, only confined to being mentioned as implementing actors in the National Action Plans (NAPs) adopted by governments in these situations. Drawing policy recommendations to governments in these contexts to invest in operationalizing this engagement, and promoting the strengthened collaboration between private companies and NGOs is therefore key for achieving impactful projects. The thesis adds to the available literature on women’s economic empowerment and GBV in post-conflict settings, as well as the private sector’s engagement in post-conflict settings. It contributes through policy recommendations to enhancing the government’s efforts to allow and facilitate the private sector’s developmental impact in these particular settings, with a focus on the WPS agenda.